Complementary Feeding Practices Among Mothers of Rural Bangladesh; A Knowledge, Attitude, and Practice Study (KYAMC Journal, 2020)
Background. In developing countries, inadequate knowledge and cultural practice on complementary feeding (CF) is one of the main reasons for malnutrition.Objective: This study aimed to document the knowledge, attitude, and practices pertaining to CF among the mothers of rural area in Bangladesh.Materials and Methods: A communitybased cross-sectional study was conducted in upazila health complex, kachua, Chandpur from July to December, 2017. A total 408 mothers of the babies aged 6-24 months and children under six months were included. Data were collected from the mothers/caregivers of the children in a pretested semi-structured data collection sheet and analyzed by SPSS version 20. Appropriate statistical tests were done. Statistical significance was considered if p value was